2018
DOI: 10.18203/2320-6012.ijrms20181453
|View full text |Cite
|
Sign up to set email alerts
|

Comparative trends of accidental to intentional mortalities over a one-year period at a tertiary care centre

Abstract: Background: The trends of deaths due to unnatural incidents are on the rise each year throughout the world, including India. Incremental trends have been observed in all mortalities throughout the country. Although all these mortalities seem preventable, yet not much has been achieved over the years. Intentional mortalities are yet more preventable as compared to non intentional ones. The trends of unnatural deaths were observed at a tertiary care centre of the capital city of Rajasthan to determine the compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(11 reference statements)
0
1
1
Order By: Relevance
“…Bansude et al in their study observed cause of death by trauma is 38.09%, burn injury 26.73%, Asphyxia 9.8% and poisoning was 21.21%, 19 where the death due to trauma is consistent with the current study. Sharma et al found death due to burn injury as a cause of death was 7%, hanging is 5%, 20 which differs from the current study as death due to hanging cases are higher in number than those due to injury cases.…”
Section: Cause Of Death Wise Analysiscontrasting
confidence: 99%
“…Bansude et al in their study observed cause of death by trauma is 38.09%, burn injury 26.73%, Asphyxia 9.8% and poisoning was 21.21%, 19 where the death due to trauma is consistent with the current study. Sharma et al found death due to burn injury as a cause of death was 7%, hanging is 5%, 20 which differs from the current study as death due to hanging cases are higher in number than those due to injury cases.…”
Section: Cause Of Death Wise Analysiscontrasting
confidence: 99%
“…20 differs from the current study as death due to hanging cases are higher in number than those due to injury cases. 22 Romana Malik et al, in their study, reported that the causes of death were distributed as follows: 40% due to Road Traffic Accidents (RTA), 31% from blunt injuries, 19% from sharp injuries, 2% from sexual assault, 4% from poisoning, and 4% from firearm cases. 19 In a study conducted in Ethiopia by Solano, the causes of death in forensic science were found to be due to strangulation (7.5%), suffocation (0.8%), others (0.5%), hanging (88%), poisoning (10%), bullet (0.7%), drowning (8.5%), electric current injury, and burn (0.8%).…”
Section: Discussionmentioning
confidence: 99%